Moving Beyond "Sinicization" and "Manchu Characteristics": Can Research on Qing History Take a Third Path?. Issue 1 (2nd January 2016) - Nianqun, Yang
EDITOR'S ABSTRACT: Yang proposes to marry the many insights procured by New Qing History to the idea of "Hua-ization, " the alternative to the sinicization thesis, by internalizing the multidirectional blending of ethnic communities. This proposed third path would combine and integrate valuable insights from both the old Qing history and New Qing History schools.